Pathogenicity of entomopathogenic fungi on three species of coffee plant mites - Cavalcanti, Ricardo Sousa; Reis, Paulo Rebelles; Moino Junior, Alcides; Altoé, Bernardo Falqueto; Franco, Renato André; Carvalho, Thaiana Mansur Botelho de (Coffee Science - ISSN 1984-3909, 1970)
Brevipalpus phoenicis (Geijskes, 1939) and Oligonychus ilicis (McGregor, 1917) (Acari: Tenuipalpidae, Tetranychidae) are considered the main pest mites of coffee plants (Coffea spp.), causing damages such as leaf fall and reduction of the photosynthetic foliar area. Among their main natural enemies, the entomopathogenic fungi and predatory mites have great potential for biological control. However, the entomopathogenic fungi can, occasionally, also infect the predatory mites. The objective of this work was to evaluate the pathogenicity of entomopathogenic fungi to the pest mites B. phoenicis and O. ilicis and to the predatory mite Iphiseiodes zuluagai Denmark & Muma, 1972 (Acari: Phytoseiidae). The experiments were carried out in a laboratory, using four strains of the entomopathogenic fungi Beauveria bassiana (Bals.) Vuill. and one of the Lecanicillium sp. The mites were exposed to the fungi by spraying the pathogen in a Potter tower. For the B. phoenicis mite, the Lecanicillium sp. UFLA 70 strain caused 100% mortality in three days of exposure. For the O. ilicis species, the most effective treatments were UFLA 13 (B. bassiana) and UFLA 70 (Lecanicillium sp.) strains, which caused 70% of mortality. Most of the tested fungi strains were not pathogenic to the predator I. zuluagai, causing low mortality. Of all the fungi tested in this experiment, the most effective for B. phoenicis and O. ilicis was UFLA 70 of Lecanicillium sp., which caused high mortality of these pests, but did not cause a high mortality rate of the predatory mite I. zuluagai.